Looking Back at the Ethical Tangles of Pediatric AIDS - Zuger, Abigail (The Hastings Center report, 2017)
The place is San Francisco, the year 1981. The newly minted young doctor, all shiny confidence, sits at his desk. Suddenly, he stares down at a lab result, startled (cue the ominous introductory chords). This opening scene can mean only one thing in a medical memoir: the mysterious disease not yet known as AIDS has come to town. As the generation who first encountered AIDS ages into its memoir-writing years, we will be seeing more of these first chapters, and despite their inevitable redundancies, each may well bring something unique to the table. Every illness subsumes many worlds, but the AIDS epidemic in particular has contained multitudes, each smaller epidemic whirling at a different speed and spinning out a different set of urgencies. In Lethal Decisions: The Unnecessary Deaths of Women and Children from HIV/AIDS, Arthur Ammann offers a comprehensive if problematic account from the world of pediatric AIDS.